Identification of a novel biomarker for pyridoxine‐dependent epilepsy: Implications for newborn screening. Issue 3 (11th March 2019) - Wempe, Michael F.; Kumar, Amit; Kumar, Vijay; Choi, Yu J.; Swanson, Michael A.; Friederich, Marisa W.; Hyland, Keith; Yue, Wyatt W.; Van Hove, Johan L. K.; Coughlin, Curtis R.
Abstract: Pyridoxine‐dependent epilepsy (PDE) is often characterized as an early onset epileptic encephalopathy with dramatic clinical improvement following pyridoxine supplementation. Unfortunately, not all patients present with classic neonatal seizures or respond to an initial pyridoxine trial, which can result in the under diagnosis of this treatable disorder. Restriction of lysine intake and transport is associated with improved neurologic outcomes, although treatment should be started in the first year of life to be effective. Because of the documented diagnostic delay and benefit of early treatment, we aimed to develop a newborn screening method for PDE. Previous studies have demonstrated the accumulation of Δ 1 ‐piperideine‐6‐carboxylate and α‐aminoadipic semialdehyde in individuals with PDE, although these metabolites are unstable at room temperature (RT) limiting their utility for newborn screening. As a result, we sought to identify a biomarker that could be applied to current newborn screening paradigms. We identified a novel metabolite, 6‐oxo‐pipecolate (6‐oxo‐PIP), which accumulates in substantial amounts in blood, plasma, urine, and cerebral spinal fluid of individuals with PDE. Using a stable isotope‐labeled internal standard, we developed a nonderivatized liquid chromatography tandem mass spectrometry‐based method to quantify 6‐oxo‐PIP. This method replicates the analytical techniques used in many laboratories and could be used with few modifications in newborn screening programs. Furthermore, 6‐oxo‐PIP was measurable in urine for 4 months even when stored at RT. Herein, we report a novel biomarker for PDE that is stable at RT and can be quantified using current newborn screening techniques.